2013
DOI: 10.1007/s13300-012-0016-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Voglibose on the Pharmacokinetics of Dapagliflozin in Japanese Patients with Type 2 Diabetes

Abstract: IntroductionDapagliflozin is an orally administered selective sodium-glucose cotransporter 2 (SGLT2) inhibitor under development for the treatment of type 2 diabetes mellitus (T2DM). Dapagliflozin lowers blood glucose through a reduction in renal glucose reabsorption. This study was performed to assess the effect of the oral antidiabetic agent voglibose [0.2 mg thrice daily (t.i.d.)] at steady-state, on the pharmacokinetics, safety and tolerability of dapagliflozin administered as a single oral dose (10 mg) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…cytochrome P450) or transporters . No clinically meaningful drug–drug interactions have been observed between dapagliflozin and commonly co‐administered oral antihyperglycaemic medications, such as metformin, pioglitazone, glimepiride, sitagliptin and voglibose , or with other agents often prescribed in patients with T2DM (warfarin, simvastatin, valsartan and digoxin) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cytochrome P450) or transporters . No clinically meaningful drug–drug interactions have been observed between dapagliflozin and commonly co‐administered oral antihyperglycaemic medications, such as metformin, pioglitazone, glimepiride, sitagliptin and voglibose , or with other agents often prescribed in patients with T2DM (warfarin, simvastatin, valsartan and digoxin) .…”
Section: Introductionmentioning
confidence: 99%
“…cytochrome P450) or transporters [12,13]. No clinically meaningful drug-drug interactions have been observed between dapagliflozin and commonly co-administered oral antihyperglycaemic medications, such as metformin, pioglitazone, glimepiride, sitagliptin and voglibose [14,15], or with other agents often prescribed in patients with T2DM (warfarin, simvastatin, valsartan and digoxin) [16]. In a first exploratory study of dapagliflozin as add-on therapy to insulin in patients with T1DM, dapagliflozin was found to have acceptable short-term tolerability and predictable pharmacokinetic and pharmacodynamic profiles [17], as previously observed for patients with T2DM [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of dapagliflozin in patients insufficiently controlled with glimepiride resulted in significant reduction in HbA 1c with only a slightly increased risk of hypoglycaemia [29] . A Japanese study demonstrated that voglibose, an alpha-glucosidase inhibitor, does not modify the PK of dapagliflozin [30] . Several clinical studies have confirmed that dapagliflozin is effective and safe when combined with other glucose-lowering agents for the management of T2DM [20] .…”
Section: Dapagliflozinmentioning
confidence: 99%
“…[3]. Although some slight alterations in SGLT2 inhibitor exposure have been documented during coadministration of some glucose-lowering agents (Table 1), these are not considered to be clinically relevant [12][13][14][15][16][17][18].…”
Section: May Be Used With a Number Of Other Agentsmentioning
confidence: 99%
“…Selected pharmacokinetic parameters and drug interactions associated with sodium-glucose cotransporters type 2 inhibitors, as reviewed by Scheen[3] Effect of co-administration on exposure to SGLT2 inhibitor/other glucose-lowering agent[12][13][14][15][16][17][18] CYP cytochrome P450, NR not reported, OAT3 organic anion transporters type 3, SGLT2 sodium-glucose cotransporters type 2, UGT uridine diphosphate-glucuronosyltransferase, $ indicates no change, : indicates slight non-clinically relevant increase, :: indicates clinically relevant increase, ; indicates slight non-clinically relevant decrease, ;; indicates clinically relevant decrease Use safely with other glucose-lowering agents Dapagliflozin, canagliflozin and empagliflozin do not appear to significantly influence the pharmacokinetics of other glucose-lowering agents(Table 1)…”
mentioning
confidence: 99%